Coronary Artery Aneurysms: A Review of the Epidemiology, Pathophysiology, Diagnosis, and Treatment - Abou Sherif, Sara; Ozden Tok, Ozge; Taşköylü, Özgür; Goktekin, Omer; Kilic, Ismail Dogu (Frontiers in Cardiovascular Medicine, 2017)
Coronary artery aneurysms (CAA) are uncommon and describe a localized dilatation of a coronary artery segment more than 1.5-fold compared with adjacent normal segments. The incidence of CAAs varies from 0.3% to 5.3%. Ever since the dawn of the interventional era, CAAs have been increasingly diagnosed on coronary angiography. Causative factors include atherosclerosis, Takayasu arteritis, congenital disorders, Kawasaki disease, and percutaneous coronary intervention. The natural history of CAAs remains unclear; however, several recent studies have postulated the underlying molecular mechanisms of CAAs and genome wide association studies have revealed several genetic predispositions to CAA. Controversies persist regarding the management of coronary artery aneurysms, and emerging findings support the importance of an early diagnosis in patients predisposed to CAAs, such as in children with Kawasaki disease. This review aims to summarise the present knowledge of coronary artery aneurysms and collate the recent advances regarding the epidemiology, etiology, pathophysiology, diagnosis, and treatment of this disease.